Teh Hijau (Camellia Sinensis) dapat Menurunkan Profil Lipid pada Pasien Dislipidemia: Kajian Pustaka - Gita Puspa Mahardhika; Yuke Andriane; Riri Risanti (Bandung Conference Series: Medical Science, 2022)
Abstract. Dyslipidemia is a lipid metabolism disorder that causes an increase or decrease in the lipid fraction of the plasma. Dyslipidemia is a risk factor for diseases with high mortality rates, such as cardiovascular disease. World Health Organization (WHO) stated there are 2.6 million deaths due to dyslipidemia per year. Fifty-three percent of dyslipidemic patients did not comply with treatment due to fear of side effects. Non-adherence to hypolipidemic drugs causes an increase in cardiovascular events and mortality, hence alternative therapy needs to be considered. Green tea contains epigallocatechin gallate (EGCG), epicatechin gallate (ECG), epigallocatechin (EGC), and epicatechin (EC) which can lower lipid profiles by various mechanisms. Catechins with gallate esters in green tea decrease the synthesis of cholesterol and triglycerides by interfering with emulsification, hydrolysis, micelle formation, and lipid absorption in the intestinal lumen. EGCG can lower LDL by increasing LDL-R expression. Abstrak. Dislipidemia merupakan kelainan metabolisme lipid yang menyebabkan adanya peningkatan atau penurunan fraksi lipid dalam plasma. Dislipidemia menjadi faktor risiko dari penyakit – penyakit dengan tingkat mortalitas tinggi, seperti penyakit kardiovaskular. Berdasar atas data dari Organisasi Kesehatan Dunia (WHO) mengatakan terdapat 2,6 juta kematian akibat dislipidemia per tahunnya. Terdapat 53% pasien dislipidemia yang tidak patuh menjalani pengobatan karena takut akan efek samping yang ditimbulkan. Ketidakpatuhan penggunaan obat dislipidemia ini menyebabkan peningkatan kejadian kardiovaskular dan kematian sehingga terapi alternatif perlu dipertimbangkan. Teh hijau mengandung epigallocatechin gallate (EGCG), epicatechin gallate (ECG), epigallocatechin (EGC), dan epicatechin (EC) yang dapat menurunkan profil lipid dengan berbagai mekanisme. Catechin dengan ester gallate pada teh hijau dapat mengganggu proses emulsifikasi, hidrolisis, pembentukan misel, dan penyerapan lipid di lumen usus sehingga sintesis kolesterol dan trigliserid menurun. EGCG dapat menurunkan LDL dengan meningkatkan ekspresi LDL-R.